Manifold design for a marine diesel air intake system - Ahlm, Per; Froode, Erik (My University, 2011)
The performance of the air intake system in a diesel engine could limit the overall engine performance. The intake manifold is an important part of the air intake system where enough air should be guided to the cylinder. Compactness is a conflicting feature to performance as engine rooms in general, and thereby engines, should use little space. Thus, the development of an air intake manifold requires knowledge about function and placement of most other parts in the engine so that a compatible and compact air intake manifold can be created. MarineDiesel AB is a Swedish company from Ängelholm developing and manufacturing marine diesel engines. The Master thesis project work has been performed in a real project where an engine, previously used in a train, is converted into a marine engine with twice the power. The engine must be designed to fit with the new requirements of the customer. These requirements directly affect the air intake system which must, as all other engine system, match the desired performance. A well-defined development process with theoretical and practical research together with company guidelines and engineering assessments has generated the concepts in this product development master thesis project. Two different intake manifold concepts have been created. The concepts are different in aspect to both manifold design and air intake system configuration. The air intake system and the manifold are dependent and therefore a feasible system concept has also been developed to each of the concepts. The performance of the concepts has been verified through flow simulation and the development process has secured their feasibility. The focus has been set on creating flexible feasible concepts that are possible to manufacture when adapted to future requirements. This creates the best possible prerequisites of implementation later in the project. In other words, the design limitations should be low in this stage of the project and thus the two final concepts are only conceptual and not ready for production. Worth mentioning is that the OEM manifold capabilities are deemed to be sufficient for implementation with both system concepts, replacing the manifold concept
Keywords: Transport; Hållbar utveckling; Farkostteknik; Konstruktionsteknik; Transport; Sustainable Development; Vehicle Engineering; Construction engineering